Fullerenol inhibits tendinopathy by alleviating inflammation - Jiao, Xin; Wang, Zengguang; Li, Yiming; Wang, Tianchang; Xu, Chen; Zhou, Xianhao; Gan, Yaokai (Frontiers in Bioengineering and Biotechnology, 2023)
Tendinopathy is a common disease in orthopaedics, seriously affecting tendon functions. However, the effects of non-surgical treatment on tendinopathy are not satisfactory and surgical treatments possibly impair the function of tendons. Biomaterial fullerenol has been proved to show good anti-inflammatory effects on various inflammatory diseases. For in vitro experiments, primary rat tendon cells (TCs) were treated by interleukin-1 beta (IL-1β) combined with aqueous fullerenol (5, 1, 0.3 μg/mL). Then inflammatory factors, tendon-related markers, migration and signaling pathways were detected. For in vivo experiments, rat tendinopathy model was constructed by local injection of collagenase into Achilles tendons of rats and fullerenol (0.5, 1 mg/mL) was locally injected 7 days after collagenase injection. Inflammatory factors and tendon-related markers were also investigated. Fullerenol with good water-solubility showed excellent biocompatibility with TCs. Fullerenol could increase expression of tendon-related factors (Collagen I and tenascin C) and decrease expression of inflammatory factors (matrix metalloproteinases-3, MMP-3, and MMP-13) and reactive oxygen species (ROS) level. Simultaneously, fullerenol slowed the migration of TCs and inhibited activation of Mitogen-activated protein kinase (MAPK) signaling pathway. Fullerenol also attenuated tendinopathy in vivo, including reduction of fiber disorders, decrease of inflammatory factors and increase of tendon markers. In summary, fullerenol is a promising biomaterial that can be used to treat tendinopathy.